IBM Storwize V5000 family products - Enders, Frank; Tate, Jon; Kubin, Sergey (IBM Corporation, IBM Redbooks, 2019)
This IBM® Redbooks® publication provides an introduction and overview of the latest products in the IBM FlashSystem® 5000 Family, including their hardware and software features.
Number on back cover: SG24-8449-00. - Includes bibliographical references. - Online resource; title from cover (Safari, viewed October 11, 2019)
Keywords: Storage area networks (Computer networks); Computer storage devices; Information storage and retrieval systems -- Business; Réseaux de stockage (Informatique); Ordinateurs; Mémoires; Systèmes d'information; Affaires; Information storage and retrieval systems; Business